Pitfall - Teshigahara, Hiroshi 1927-2001; Abe, Kōbō 1924-1993; Segawa, Hiroshi; Igawa, Hisashi; Tanaka, Kunie; Kanze, Hideo (Criterion Coll., 2007)
A man wanders into a seemingly deserted town with his young son in search of work.
Aspect ratio 1.33:1. - New, restored high-definition digital transfer
Orig.: Japan 1962
Enth. video essay on the film by critic and festival programmer James Quandt
Keywords: Fathers and sons -- Drama; Feature films; Feature films -- Japanese language; Ghost towns -- Drama; Ghosts -- Drama; Unemployed -- Drama